Implementation of Islamic Business Ethics in Conventional Bank BRI Ciamis Branch Office, West Java - Hisam Ahyani; Haris Maiza Putra; Memet Slamet; Muharir Muharir; Andri Nugraha (Banque Syar'i: Jurnal llmiah Perbankan Syariah, 2023)
The purpose of this study is to find out the model and implementation of Islamic business ethics carried out by Bank BRI Ciamis branch office, where in carrying out its business it has put forward the principles of Islamic business ethics in serving consumers. The academic problem that arises is that Bank BRI KC Ciamis is a non-sharia bank, but in service to consumers it prioritizes Islamic business ethical values such as being fair, honest, trustworthy, besides that the majority of Bank BRI KC Ciamis employees are Muslims. The author tries to reveal and dig into this research using descriptive analysis where data sources are obtained through technical interviews, observation and documentation. The findings of this study are that the implementation of business at BRI KC Ciamis bank prioritizes the principles of Islamic business ethics, this can be proven in the 10 behaviors of BRI personnel, including: 1) Excellent Service, 2) employees work 3) effectively and 4) efficiently and 5) prioritizing responsibility, 6) honest, 7) mutual respect, 8) full of innovation, 9) positive attitude and 10) prioritizing trust in consumers. As for added value, namely the brand of BRI bank, namely "serving with sincerity." Abstrak: Tujuan penelitian ini yakni untuk mengetahui model dan pelaksanaan etika bisnis islami yang dilakukan oleh Bank BRI kantor cabang Ciamis, dimana dalam pelaksanaan bisnisnya ia telah mengedepankan prinsip-prinsip etika bisnis islami dalam melayani konsumen. Adapun problem akademik yang muncul adalah Bank BRI KC Ciamis adalah bank non-syariah, namun dalam pelayanan kepada konsumen mengedepankan nilai-nilai etika bisnis islami seperti besikap adil, jujur, amanah, selain itu mayoritas pegawai Bank BRI KC Ciamis beragama islam. Penulis berusaha menguak serta menggali dalam penelitian ini menggunakan analisis deskriptif dimana sumber data diraih melalui teknis wawancara, observasi serta dokumentasi. Hasil temuan penelitian ini menyatakan bahwa pelaksanaan bisnis di bank BRI KC Ciamis mengedepankan prinsip etika bisnis islami, hal ini dapat dibuktikan dalam 10 Prilaku insan BRI, meliputi: 1) Pelayanan Prima, 2) karyawan bekerja secara 3) efektif dan 4) efisien serta 5) mengedepankan tanggungjawab, 6) jujur, 7) saling menghargai, 8) penuh inovatif, 9) sikap positif dan 10) mengedepankan kepercayaan kepada konsumen. Adapun sebagai nilai tambah yakni brand dari bank BRI yakni" melayani dengan setulus hati."